Ezra Pound - Kuberski, Philip (Gainesville : University Press of Florida, 1960)
That the beauty of Ezra Pound's late Cantos can appear - on the same page - with the rankest anti-Semitism continues to be a problem worth serious discussion, as well as a problem in the understanding of modernism. Philip Kuberski locates the central tension between Pound's poetry and his politics in the contrast between the poet's technical innovations - his commitment to modernist writing - and his antimodernist conception of reading and esthetics. Few twentieth-century poets, Kuberski says, have been "as dedicated to a reconciliation of metaphysical values and the materiality of human languages." Focusing on this juncture of form and meaning, he asserts that Pound's work presents "a dramatic, perhaps tragic, illustration of the costs involved in moving from a theocentric or logocentric understanding of art to a truly modern or postmodern understanding of it." Kuberski also considers the ways in which Pound's career reflects an extreme version of tensions in American culture. Both Pound's poetry and his fascism can be derived from elements of American Romanticism, he claims, citing Emerson's exposition of "natural" language, Whitman's sense of the poet as Adamic Superman, and Poe's exploration of nonalphabetic scripts. In his title and his terminology, Kuberski employs the metaphor of stones, a calculating device, to chart Pound's overt concerns with a stone-like foundation for human knowledge, for origin, and for civilization.
A calculus of Ezra Pound -- In the American archive -- The economy of romance -- Anti-semitism and the enlightenment of signs -- Totalitarian history -- Pound's sacred technology.
Includes bibliographical references (pages 197-200) and index.
Print version record.
Keywords: Pound, Ezra, -- 1885-1972 -- Criticism and interpretation; Pound, Ezra, -- 1885-1972.; Pound, Ezra, -- 1885-1972.; National characteristics, American, in literature; POETRY -- American -- General; National characteristics, American, in literature; Electronic books; Criticism, interpretation, etc